System downtime in financial accounting: challenges and strategic solutions - Mohd Ashri, Nur Asniah; Wan Ahmad, Wan Noraswaniaty (Faculty of Accountancy, Universiti Teknologi MARA (UiTM) Cawangan Kelantan, 2025)
The reliability of financial accounting systems is important as to ensure the accurateness of transaction processing, compliance with regulatory requirement, and meeting the timely reporting. However, as organizations become increasingly more relying on digital tools, they are more expose to system downtime. System downtime can interrupt financial operations and create substantial challenges. This study examines the impact of system downtime on financial accounting, aiming on its effects on productivity, financial stability, and workforce efficiency. It looks into several key challenges, including operational disruptions, financial losses, and increased error rates. Additionally, this study suggests and discusses some effective mitigation strategies, such as implementing automation in backup systems, improving employee training, and ensuring routine and schedule system maintenance. By strengthening IT resilience, financial institutions can minimalize risks related with financial inaccuracies and regulatory non-compliance, ensuring the steadiness and reliability of their accounting systems in an increasingly digital financial landscape.